RACE IDENTITY OF INDIAN PLASMOPARA HALSTEDll, CAUSE OF DOWNY MILDEW OF SUNFLOWER - C. D. MAYEE, M. A. PATIL AND (Indian Phytopathology, 2002)
Races of Plasmopara halstedii, cause of downy mildew of sunflower, are well characterized in Europe and America. Reactions of Indian culture using oosporic and zoosporangial inoculations on four differential sunflower lines, RHA265, RHA273, RHAÂ·274 and cv Progress were determined over a period of three years. Consistent resistant reaction of all three RHA differentials and susceptible reaction of cv Progress confirmed the identity of Indian isolate as European Race-I.